A Research on Female Labour Force Participation in Malaysia - Low Choon Wei; Loh Yunn Cinn (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Human resource is one of the key determinants for development in terms of social, economic, political, and even technological. Despite the efforts Malaysia has made to narrow down gender inequality and to promote women’s economic inclusion, the participation rate of women in the labour market remains low. Ordinary Least Square (OLS) regression were employed in this study for analysis purposes. Variables involved are the fertility rate, age dependency ratio, economic growth, women's education, and female labour participation rate in the context of Malaysia. The empirical study uses time-series data from 1982 to 2019. The empirical result of this paper concludes that all the selected explanatory variables have a substantial influence on female labour participation. Age dependency rate has a significant negative relationship, otherwise positive. The result of this paper has significant implications that would have the potential to address the issues faced by the female workforce